Relationship Between Farmer Characteristics and Farmer Group Dynamics with The Success of Farmer Empowerment Programs Through Agricultural Technology and Information - Aisyah, Siti; Faqih, Achmad; Rahudi, Rahudi; Falah, M. Aep Samsul; Setiawan, Danis; Apriansyah, Bayu (Green Publisher Indonesia, 2023)
Extension activities managed by farmers as a process of changing the behavior, mindset and attitude of farmers from traditional subsistence farmers to modern farmers with agribusiness insight through continuous learning are carried out with a learning by doing approach that focuses on developing managerial capacity, leadership and entrepreneurship of key actors in order to realize reliable agribusiness entrepreneurs. This study aims to examine how the relationship between farmer characteristics and group dynamics on the success rate of agricultural technology and information programs in the Tunas Walahir II Farmer Group, Pakapasan Hilir Village, Hantara District, Kuningan Regency from July to September 2022 with a sample of 25 farmers. This study used descriptive quantitative methods with data collection techniques through interviews. The data in this study is in the form of primary and secondary data. The analysis activities use the Spearman Level Correlation Coefficient Test (rs). The results showed that there was a real relationship between the characteristics of farmers (area of arable land and farming experience) with the success of agricultural technology and information programs, while the age of farmers and the level of education of farmers had no real relationship with the success of agricultural technology and information programs. There is a clear relationship between the dynamics of farmer groups and the success of agricultural technology and information programs.